Prevalence of positive islet autoantibody in type 2 diabetes patients: a cross-sectional study in a Chinese community - Gao, Xiangyu (Endocr Connect, 2019)
BACKGROUND: Islet autoantibodies occur in type 2 diabetes. Our study aimed to investigate the prevalence of positive islet autoimmunity in community patients with type 2 diabetes. METHODS: A total of 495 community patients with type 2 diabetes were recruited using the method of cluster sampling in this cross-sectional study. Three islet autoantibodies including glutamic acid decarboxylase antibody (GADA), insulin autoantibody (IAA) and islet cell antibody (ICA) were measured, and clinical characteristics involved in those individuals were evaluated. RESULTS: The positive rate of islet autoantibodies was 28.5% in total, while combinations of different autoantibodies were rarely seen. Compared with GADA-negative group, positive counterparts significantly tended to have lower levels of body mass index (BMI), waist-hip ratio (WHR), and urinary microalbumin (mALB) (P < 0.05). Adjusted for confounding factors, WHR, triglycerides (TG), and mALB seemed to be negative independent predictors of GADA (OR < 1, P < 0.05). Patients with positive IAA tended to receive insulin treatment (P < 0.0001). Besides, fasting blood glucose (FBG), serum levels of high-density lipoprotein cholesterol (HDL-CH), aspartate transaminase (AST), and γ-glutamyltransferase (GGT) were more likely to be higher in IAA positive subgroup in comparison with the negative counterparts. While after AST was adjusted by unconditional logistic regression analysis, history of insulin treatment, FBG, HDL-CH, and GGT were confirmed as positive predictors of IAA. Furthermore, in patients who were IAA positive, those treated with exogenous insulin tended to have longer duration of diabetes than non-insulin treatment counterparts (P < 0.0001). With regard to ICA, however, there were no significant differences between the two subgroups, except that serum level of AST/ALT seemed to be slightly different (P = 0.064). CONCLUSION: These data suggested that type 2 diabetic community patients with positive GADA tended to be lean and were able to maintain normal lipid metabolism, while patients with positivity of IAA were frequently accompanied with insulin treatment and more closely associated with diabetic liver damage.